2017
DOI: 10.1002/ejsp.2281
|View full text |Cite
|
Sign up to set email alerts
|

Implicit self and the right hemisphere: Increasing implicit self‐esteem and implicit positive affect by left hand contractions

Abstract: Unilateral hand contraction typically activates the contralateral hemisphere and has led to changes in psychological states and performances in previous research. Based on a right hemisphere model of the implicit self, we hypothesized and found that left hand contraction increases momentary levels of implicit self‐esteem (Studies 1 and 2) and implicit positive affect (Study 3). The findings are discussed with respect to potential differences between the hemispheres in implicit and explicit affective processing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 93 publications
(145 reference statements)
2
9
0
Order By: Relevance
“…In addition, recent studies suggest that the right hemisphere even contributes to the unconscious regulation of emotions. For example, Quirin, Bode, Fröhlich and Kuhl () found that activating the right hemisphere by squeezing a stress ball with the contralateral hand led to increases of implicit self‐esteem and implicit positive affect, but had no effects on explicit self‐esteem or explicit positive affect. Extended self‐development: integrative competence …”
Section: The Conceptual Self Versus the Integrated Selfmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, recent studies suggest that the right hemisphere even contributes to the unconscious regulation of emotions. For example, Quirin, Bode, Fröhlich and Kuhl () found that activating the right hemisphere by squeezing a stress ball with the contralateral hand led to increases of implicit self‐esteem and implicit positive affect, but had no effects on explicit self‐esteem or explicit positive affect. Extended self‐development: integrative competence …”
Section: The Conceptual Self Versus the Integrated Selfmentioning
confidence: 99%
“…These include the ability to cope with negative experiences by intuitively recruiting positive affect (Quirin, Bode, & Kuhl, ; Koole & Jostmann, ; see also Koole, ). Notably, activating the right hemisphere by squeezing a stress ball with the left hand leads to increases in implicit positive affect and implicit self‐esteem (Quirin et al, ). Moreover, the right hemisphere supports perspective taking and the inclination to deem others trustworthy (Winston et al, ) in addition to affect regulation and self‐development (Schore, , ).…”
Section: The Conceptual Self Versus the Integrated Selfmentioning
confidence: 99%
“…There are experimental ([8], [31], [32], [33]) and EEG studies ([34], [35]) showing that unilateral muscle contractions activate the contralateral hemisphere. It has been found that activation of the right hemisphere through unilateral muscle contractions reduces self-infiltration [8], enhances creative thinking [32], increases implicit self-esteem [36], and prevents chocking under pressure in athletes, presumably by suppressing conscious control of the left hemisphere [31]. We therefore included activation of the left or right hemisphere as within-participant variable in the design.…”
Section: Introductionmentioning
confidence: 99%
“…While the left hemisphere processes the information in a strictly sequential and unambiguously understood monosemantic context 81 , the function of the right hemisphere is to simultaneously capture a vast number of possible connections and to integrate them in an ambiguous but polysemantic context 81 83 . Because of this functionality, the right hemisphere has been involved in a variety of integrative phenomena 84 86 , including helping the implicit self 87 maintain a positivity bias 88 90 . The implicit self is a highly integrative construct that processes vast amounts of self-relevant information from cognitive (e.g., autobiographical memories), motivational (e.g., values, needs) and affective (e.g., emotions) systems in parallel 87 , 91 .…”
Section: Discussionmentioning
confidence: 99%
“…Because personal experiences are inherently perceived as positive in healthy individuals 92 , a functional implicit self is crucial in maintaining a positivity bias by assimilating negative affective experiences within a network of predominantly positive experiences 81 , 93 . Due to this holistic nature, the implicit self is believed to be a function of the right hemisphere 87 , 90 . The incapacity to regulate negative affect and display a (somewhat normal) positivity bias underlies emotional disorders such as depression, alexithymia and suicidal ideation, which are characterized both by a lack of optimism bias 53 and a functionally deficient right hemisphere 79 , 81 , 94 , including decreased integrity of white matter tracts 95 .…”
Section: Discussionmentioning
confidence: 99%